Cytospora juglandigena sp. nov. causing walnut branch dieback in Xinjiang, China - Zhao, Li-Li; Wang, Jia-Wen; Kong, Ting-Ting; Liu, Ai-Hua; Zhang, Ying (Phytotaxa, 2025)
Cytospora species are common pathogens associated with stem canker diseases of woody plants, with a wide range of hosts, and have a global distribution. Cytospora species have also caused serious stem disease in walnut. In this study, 67 isolates of Cytospora were collected from Juglans regia associated with symptomatic dieback and blight disease in Xinjiang, China. Morphological characterization and multi-locus phylogenetic analyses of concatenated ITS, RPB2, and tef1-α sequences demonstrated that these isolates represent a novel species. Pathogenicity tests confirmed, through Koch’s postulates, that Cytospora juglandigena is the causal agent of branch dieback in walnut.